Facile synthesis of 3-Benzylsulfinyl- and 3-Benzylsulfonyl-7-Diethylaminocoumarins. (August 2014) - Wang, Xiaolong; Xue, Ziyan; Ma, Yanying; Yang, Fang
The efficient synthesis of a 3-benzylsulfinylcoumarin and a 3-benzylsulfonylcoumarin starting from thiobenzyl alcohol using solvent-free Knoevenagel reaction as the key step is reported. Moreover, the molecular structure of 3-benzylsulfonyl-7-diethylaminocoumarin is confirmed by X-ray crystal analysis.